2014
DOI: 10.1093/humrep/deu143
|View full text |Cite
|
Sign up to set email alerts
|

Cancer in children and young adults born after assisted reproductive technology: a Nordic cohort study from the Committee of Nordic ART and Safety (CoNARTaS)

Abstract: No conflict of interest was reported. The study was supported by grants from The European Society for Human Reproduction and Embryology (ESHRE), Sahlgrenska University Hospital, Gothenburg, Sweden, the University of Copenhagen, Denmark, the Danish Agency of Science, Technology and Innovation and the Nordic Federation of Societies of Obstetrics and Gynecology (NFOG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
73
4
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(95 citation statements)
references
References 43 publications
8
73
4
7
Order By: Relevance
“…Moreover, neither parental age nor ART seems to be associated with an increased cancer risk in our study cohort. This is in line with previous findings that children born after ART are not at increased cancer risk [15,17].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, neither parental age nor ART seems to be associated with an increased cancer risk in our study cohort. This is in line with previous findings that children born after ART are not at increased cancer risk [15,17].…”
Section: Discussionsupporting
confidence: 93%
“…A total of 12 studies including 2,786,687 participants and 13,319 cases were selected in this meta-analysis of acute childhood leukemia [12][13][14][15][16][17][18][19][20][21][22][23]. The results suggested that preterm birth was significantly associated with an increased risk of acute childhood leukemia when compared to full-term birth (OR = 1.09, 95% CI = 1.02-1.17), with mild heterogeneity (I 2 = 12.0 %, P = 0.33) (Fig.…”
Section: Main Analysismentioning
confidence: 99%
“…Скандинавский Комитет по ВРТ и безопасности (CoNARTaSgroup) недавно опубликовал результаты масштабного реестрового исследования, где пред-ставлены данные о заболеваемости раком у детей, за-чатых с помощью методов ЭКО [62]. Не было выяв-лено значительного повышения рисков возникнове-ния каких-либо форм рака у детей, зачатых с исполь-зованием методов ЭКО, по сравнению с популяцией (AOR Рост, физическое и когнитивное развитие в раннем детстве у детей, зачатых с использованием методов ЭКО В ряде исследований оценивался рост детей, за-чатых с использованием методов ЭКО, по сравне-нию с детьми из общей популяции.…”
Section: заболеваемость раком после экоunclassified